2017
DOI: 10.1080/03639045.2017.1386194
|View full text |Cite
|
Sign up to set email alerts
|

A novel intracellular pH-responsive formulation for FTY720 based on PEGylated graphene oxide nano-sheets

Abstract: PEGylated GO can act as a pH-responsive drug carrier to improve the efficacy of anticancer drug delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 45 publications
3
9
0
Order By: Relevance
“…Cytotoxicity investigations were also performed for different types of FTY720 NPs, including graphene oxide, liposomal, and calcium phosphate-based NPs. 21 , 22 , 50 As observed here, these authors also reported that cell viability decreased in a concentration-dependent manner upon incubation with FTY720 NPs.…”
Section: Resultssupporting
confidence: 85%
“…Cytotoxicity investigations were also performed for different types of FTY720 NPs, including graphene oxide, liposomal, and calcium phosphate-based NPs. 21 , 22 , 50 As observed here, these authors also reported that cell viability decreased in a concentration-dependent manner upon incubation with FTY720 NPs.…”
Section: Resultssupporting
confidence: 85%
“…The conservation of the carbon‐oxygen double bonds in mrGO, shown through the XPS measurements, could be a valuable source for chemical modifications, which are necessary for most biosensors . At the same time, the mrGO is up to 2.7 magnitudes more conductive than graphene oxide, which would enable applications requiring both chemical modification and electrical measurements (e. g. for field‐effect transistor biosensors) . The lower proportion of carbon‐oxygen single bonds in mrGO compared to GO could decrease the amount of accidentally‐bound biomolecules during biosensing in comparison to GO and, therefore, increase the selectivity of biosensors made from mrGO in comparison to GO .…”
Section: Discussionmentioning
confidence: 99%
“…[42] At the same time, the mrGO is up to 2.7 magnitudes more conductive than graphene oxide, which would enable applications requiring both chemical modification and electrical measurements (e. g. for field-effect transistor biosensors). [42,43] The lower proportion of carbon-oxygen single bonds in mrGO compared to GO could decrease the amount of accidentallybound biomolecules during biosensing in comparison to GO and, therefore, increase the selectivity of biosensors made from mrGO in comparison to GO. [44] The improved storability of mrGO in water coupled with the 2.7 orders-of-magnitude increase in conductance may be beneficial for conductive inks as well.…”
Section: Discussionmentioning
confidence: 99%
“…Introducing tunable material properties of degradability and stiffness could directly influence neural progenitor cell behaviour [ 106 ] and influence adipose derived stem cell chondrogenic differentiation [ 107 ]. A pH-responsive nanocarrier based on modified graphene oxide to promote acid-triggered intracellular release of a soluble drug illustrates the sophistication that can be envisaged, allowing triggered cell-response potency assays [ 108 ]. It is likely that more elaborate tissue-engineered biosensors may become useful in biomarker discovery as functional aspects of stem cells may be dependent on 3D derived signals that are not obtained in monolayer cultures.…”
Section: Discussionmentioning
confidence: 99%